State‐of‐the‐art and comprehensive study of renewable energy sources based microgrid with single‐phase self‐excited induction generator. Issue 18 (16th February 2021) - Kalla, Ujjwal Kumar; Singh, Bhim; Kumar, Praveen; Agarwal, Kusum Lata; Murthy, S.S.
Abstract : This study presents a comprehensive study of microgrid systems using a single‐phase self‐excited induction generator (SEIG) using renewable energy sources (RESs) and their integration with other energy sources. It investigates on the use of a single‐phase two‐winding SEIG for off‐grid single‐phase power generation from different RESs. Various solid‐state controllers are implemented for each configuration. This is the first time, such an attempt is made to use a specially designed SEIG for sustainable energy application to feed single‐phase loads vastly prevalent in isolated and distant locations in accessible to the grid. This work has great importance due to the non‐availability of the power in remote regions in developing countries. Moreover, there is a need to use local RESs such as bio, hydro, wind in combination with the solar energy. The present global need to generate pollution free electricity makes this work quite important. Thus, this study presents a comprehensive review of different modes of SEIG using RESs for single‐phase power generation realising the microgrid feeding a combination of practical loads with viable and successful controllers to ensure desired quality power across loads.